Analysis of Students’ Ability in Writing a Research Proposal - M. Fadhly Farhy Abbas (Universitas Lancang Kuning, 2015)
This research is based on the needs to investigate the students’ ability in writing a research proposalfor the fourth year students at English Education Department Faculty of Teachers Training and EducationUniversity of Lancang Kuning. This research aims at analyzing the students’ ability of the fourth year students at English Education Department Faculty of Teachers Training and Education University of Lancang Kuning in writing a research proposal. The method employed in this research is qualitative method with survey research design. The total number of population in this research were 132 students. The sample elected were 20 students. Based on the data which have been collected and analyzed, it were found that the students’ ability in writing a research proposal categorized into “middle”. The average score achieved was 67.1. It was categorized into middle. Based on the research finding above, it can be concluded that the students’ ability in writing a research proposal is categorized into middle. This result is in line with the analysis of writing a research proposal using scoring rubric available in this research.